Penerapan AI dalam Pendidikan: Strategi dan Praktik Deep Learning dalam Kurikulum Pendidikan Dasar di Pulau Tidung Kepulauan Seribu - Dety Amelia Karlina; Enjang Yusup Ali; Dadan Djuanda; Riana Irawati; Sidqia Nurfadilah (Universitas Teuku Umar, 2026)
The integration of artificial intelligence (AI) into the elementary school curriculum was officially implemented by the Indonesian government in the first semester of 2025/2026. This policy requires teachers to be pedagogically prepared; however, schools in island regions such as Pulau Tidung still face challenges in terms of infrastructure, access to training, and digital competence. This community service program aimed to describe the implementation and outcomes of the program “AI Implementation in Education: Strategies and Deep Learning Practices in the Elementary Curriculum.” The methods included problem identification, program planning, interactive seminars, evaluation, and follow-up through the establishment of a teacher community, with 25 kindergarten and elementary school teachers as participants. The results indicated 100% participation, moderate improvement in understanding, enhanced practical skills in using simple AI applications, and the ability to integrate AI into lesson planning. The findings suggest that practice-based training can increase teachers’ confidence in adopting technology, although continuous mentoring remains necessary. This program contributes to bridging the digital competence gap among teachers in island regions while offering an initial model of AI integration based on deep learning in elementary education.